Sport and triad risk factors influence bone mineral density in collegiate athletes - Tenforde, A. S.; Carlson, J. L.; Sainani, K. L.; Chang, A. O.; Kim, J. H.; Golden, N. H.; Fredericson, M. (Medicine & Science in Sports & Exercise, 2018)
Purpose: Athletes in weight-bearing sports may benefit from higher bone mineral density (BMD). However, some athletes are at risk for impaired BMD with female athlete triad (Triad). The purpose of this study is to understand the influence of sports participation and Triad on BMD. We hypothesize that athletes in high-impact and multidirectional loading sports will have highest BMD, whereas nonimpact and low-impact sports will have lowest BMD. Triad risk factors are expected to reduce BMD values independent of sports participation.